A new temnospondyl from the Permo-Triassic Buena Vista Formation of Uruguay - Piñeiro, Graciela (2007)
A partial skull recovered from conglomerates of the Permo-Triassic Buena Vista Formation in Uruguay belongs to a new species, Uruyiella liminea gen. et sp. nov. This species is characterized by a broadly triangular skull with laterally projecting posterior corners, rhytidosteid-like dermal sculpturing, and orbits positioned close to the skull margin. Uruyiella liminea is distinguished from other temnospondyls by a combination of primitive and derived character states, such as the anterior extent of the palatine ramus of the pterygoid, which excludes the ectopterygoid and most of the palatine from the lateral border of the interpterygoid vacuity, and the absence of both tabular horns and otic notches. A phylogenetic analysis places Uruyiella and the enigmatic Early Triassic Laidleria in a clade to which we attach the family name Laidleriidae. The Plagiosauridae and the Laidleriidae form a clade at the base of Dvinosauria, which is the sister group of a clade that includes Stereospondyli and Archegosauroidea. This result is unexpected because Laidleria and Plagiosauridae are nested deeply within Stereospondyli in most phylogenies. The sister-group relationship of Uruyiella and Laidleria suggests that a ghost lineage for the latter genus extends down into the earliest Triassic and perhaps even into the Late Permian, which in turn would suggest survivorship of the Laidleriidae through the Permo-Triassic extinction event.